Adsorption Characteristics of Silica Gel-Water Pairs in Personal Protection Equipment - Hanif, Shazia; Adiputra, Suryadijaya; Yaningsih, Indri; Budiana, Eko Prasetya (Mekanika: Majalah Ilmiah Mekanika, 2023)
This study aims to determine the characteristics of silica gel RD to water vapor in terms of adsorption capacity and rate. A layer modeling approach was employed to simulate the Personal Protective Equipment (PPE), which comprised four distinct layers: the surrounding environment air, the fabric layer, the RD-type silica gel layer, and the air gap separating the silica gel from the skin surface. The simulation encompassed environmental conditions set at 27 ℃, while the human body's temperature was maintained at 35 ℃. This study uses a simulation method using Guggenheim–Anderson de Boer (GAB) modeling calculations to determine isothermal characteristics and Linear Driving Force (LDF) modeling to determine kinetic characteristics with an adsorbent temperature of 26.84 ℃. The simulation results show that the isothermal characteristics of silica gel RD at a relative humidity of 60% or a relative pressure of 0.6 have an absorption capacity of 0.38 kg/kg. Moreover, the kinetic characteristics of silica gel RD have an absorption rate of 0.38 kg/kg of water vapor with a time of 980 s until a significant reduction in the absorption value occurs